Weltwirtschaftsstatistik Internationale Wirtschaftsstatistik und die Geschichte der Globalisierung, 1850-1950 - Bemmann, Martin (Studien zur Internationalen Geschichte, 2023)
By looking at the development of international economic statistics, this book examines globalization processes and the dynamics that drive them. It questions widespread periodizations by showing that, from the First World War, it took accelerated globalization processes in the "material sense" to make the "de-globalization processes" visible that shaped the 1920s and 1930s for people of that time and later observers.